THE EFFECT OF SELF EFFICACY, WORK MOTIVATION AND WORK ENVIRONMENT ON TEACHER JOB SATISFACTION AT SMA NEGERI 1 LHOKSEUMAWE - Nadia Sari; Yanita; Aiyub Yahya; Faisal Matriadi; Ibrahim Qamarius (RADJA PUBLIKA, 2023)
This study aims to determine how the influence of self-efficacy, work motivation, and work environment on teacher job satisfaction in SMA Negeri 1 Lhokseumawe. The data used in this study are primary data obtained by distributing questionnaires to 72 teachers who teach at SMA Negeri 1 Lhokseumawe. The data analysis technique used is multiple linear regression analysis consisting of data instrument testing, classic assumption testing, and hypothesis testing using SPSS version 26. The results of the study conclude that self-efficacy, work motivation, and work environment have a positive and significant effect on satisfaction teacher work at SMA Negeri 1 Lhokseumawe.